Determinants of Trade Credit in European Construction Firms: a Preliminary Study - Barbua-Misu, Nicoleta; Deari, Fitim (Ekonomika, 2016)
The aim of this paper is to present a comparative study of trade credit indicators and the possible determinants of trade credit for firms acting in the construction sector, using a sample of 958 medium and large firms for the period 2004-2013. The objective of the study is to identify and examine selected variables that may determine trade credit used and provided by selected firms. The sample is derived from the Amadeus database. The examined firms were ones that have sold and bought on credit. The data was organised as panel-data and quantitative analyses were performed. This study demonstrates results that firms with higher trade receivables are less profitable; a positive correlation was found between trade receivables and liquidity, whereas a negative correlation was detected between trade receivables and gearing; larger firms provide and obtain more trade credit than medium firms; more profitable firms use less gearing; firms with higher profit margin are more liquid and more liquid firms use less gearing; based on an average and overall terms, there is not such a clear distinction between Western and Eastern European countries from viewpoint of net trade credit and net trade period.
Keywords: construction sector; medium and large firms; trade credit; trade period; correlation